X-Ray Diffraction and Infrared Spectroscopic Analysis of Solid Biopolymer Electrolytes Based on Dual Blend Carboxymethyl Cellulose-Chitosan Doped with Ammonium Bromide - A. A. Mejenom; M. N. Hafiza; M. I. N. Isa (Akademi Sains Malaysia, 2024)
The present work discusses the structural studies of dual blended solid biopolymer electrolytes (SBEs) based carboxymethyl cellulose (CMC)/chitosan (CS) doped with various ammonium bromide (AB) composition using solution casting technique. X-ray Diffraction (XRD) result reveal that all samples are completely amorphous except for sample Ab-30. FTIR analysis shows interaction has occurred between CMC/CS and NH4Br. Analysis of transport properties has shown that the dependency of ionic conductivity was on the ionic mobility, ? and diffusion coefficient, D of mobile ion.